Histopathological Study of Wistar Rat Liver Infected with Schistosoma japonicum - David Pakaya; Varel Bramantio Gagola; Christin Rony Nayoan; Junjun Fitriani; Vera Diana Towidjojo (WMJ (Warmadewa Medical Journal), 2024)
Schistosoma, including Schistosoma japonicum (S. japonicum), can live with an intermediate host, such as rats, and infect mammals, such as humans and rats. We can use a rat model to understand the pathophysiology of Schistosoma. The aim of this study is to describe the histopathological changes of Wistar rat liver infected with S. japonicum. This is a quasi-experimental study that employs a descriptive qualitative approach. The samples were 8-week-old male Wistar rats with an average weight of 250 to 350 g. The whole sample was made up of 16 rats that were given S. japonicum cercaria intraperitoneally. The rats were then split into 4 groups: the control group (C) ended on day 0, the T1 group ended on day 14, the T2 group ended on day 42, and the T3 group ended on day 60. We necropsied the liver, examined it histopathologically using hematoxylin eosin staining, and conducted a qualitative analysis. In the control group, we observed normal liver structure; in the T1 group, we observed hepatocyte degeneration, dilatation of liver sinusoids, and accumulation of inflammatory cells; in the T2 group, we observed similar conditions to the T1 group, including hepatocyte apoptosis; in the T3 group, we observed hepatocyte degeneration, hepatocyte necrosis, infiltration of inflammatory cells (PMNs), and thickening of connective tissue. In conclusion, there was gradual liver damage over the period of time in animal models, and the worst is in chronic conditions, which are dominated by fibrotic tissue, but no granulomas have been found.